The Effect Of Employee Recruitment And Placement On Employee Work Productivity At PT Agro Wijaya Industri (AWI) Koto Rayo Village, Tabir District, Merangin Regency - Roni, Khairun A; Novriansyah, Yudhi (Baselang, 2023)
This research purpose is to analyze the effect of employee recruitment and placement on employee work productivity at PT Agro Wijaya Industri (AWI) Koto Rayo Village, Tabir District, Merangin Regency. Research used quantitative method. The research population is employees of PT Agro Wijaya Industri (AWI) and then,  research sample was 59 peoples of factory employees.. Result of the research showed that the Recruitment Variable (X1) obtained a value of t-count (2.701) t-table (2.003) and the Employee Placement Variable (X2) obtained a value of t-count (4.114) t-table (2.003), a simultaneous test obtained a value of F-count of 32.435 greater than F-table of 3,160. So it can be concluded that the recruitment (X1) and employee placement (X2) variables partially or simultaneously have a positive and significant effect on the work productivity (Y) of PT employees. Agro Wijaya Industri, Merangin Regency. Based on the Summary Model output above, it can be seen that the R Square value is 0.537 or 53.7%. Where the dependent variable (Y) can be explained by the two independent variables at 53.7%, while the remaining 46.3% is influenced by other dimensions outside the research